2020
DOI: 10.1002/elan.202000049
|View full text |Cite
|
Sign up to set email alerts
|

MnO2 Nanoclusters Decorated on GrapheneModified Pencil Graphite Electrode for Non‐Enzymatic Determination of Cholesterol

Abstract: Electrochemically deposited MnO 2 on graphene coated Pencil Graphite Electrode (PGE) has been used to develop a facile electrochemical sensor for the determination of Cholesterol. Cyclic voltammetric (CV) studies and electrochemical impedance spectroscopic (EIS) technique were used to investigate the electrochemical properties of the modified sensing platform. The physicochemical properties of the modified electrodes were characterized by X-ray photoelectron spectroscopy (XPS), Scanning electron microscopy (SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…The above-mentioned process was repeated to trim down the graphene layer for achieving improved-quality graphene. 25,35–37 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The above-mentioned process was repeated to trim down the graphene layer for achieving improved-quality graphene. 25,35–37 …”
Section: Resultsmentioning
confidence: 99%
“…The above-mentioned process was repeated to trim down the graphene layer for achieving improved-quality graphene. 25,[35][36][37] Preparation of ZnO/GR/PGE. PGE with a dimension of 0.65 cm 2 was pretreated with 1.0 M H 2 SO 4 and rinsed in doubledistilled water.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that the electrode showed a wide linear range for the measurement of cholesterol, from 12 × 10 −10 M to 240 × 10 −10 M, under optimum conditions, with a low detection limit of 0.42 nM. The results demonstrated that the electrode has excellent sensitivity for cholesterol [77]. Rison et al, as illustrated in Figure 10, reported a non-enzymatic cholesterol biosensor based on MnO2 nanoclusters immobilized on a graphene-modified pencil graphite electrode (MnO2/GR@PGE).…”
Section: Zhu Et Al and Narvaez Et Al Reported Various Graphene And Re...mentioning
confidence: 86%
“…It has been found that the electrode showed a wide linear range for the measurement of cholesterol, from 12×10 −10 M to 240×10 −10 M, under optimum conditions, with a low detection limit of 0.42 nM. The results demonstrated that the electrode has excellent sensitivity for cholesterol [77]. Agnihotri et al presented a non-enzymatic approach toward cholesterol detectionusing β-cyclodextrin-functionalized graphene.…”
Section: Zhu Et Al and Narvaez Et Al Reported Various Graphene And Re...mentioning
confidence: 99%